Peking/Ningbo, China: Unterwasserarchäologie - Hosner, Dominic (e-Forschungsberichte des DAI, 2023)
Research and protection of heritage under water, mostly shipwrecks along the “silk roads of the sea” are very high on the list of priorities in China. The National Center of Underwater Cultural Heritage in Beijing with several research bases at sea ports and lake shores is responsible for documentation, salvage and conservation of sites and finds and organizes training programs. Dominic Hosner of the DAI’s Beijing Branch Office was the first invited international underwater archaeologist to join the diving squad in 2014 for excavating cargo from a ship which sank between 1821 and 1850 off the coast near Ningbo city.